Osteopontin depletion in macrophages perturbs proteostasis via regulating UCHL1-UPS axis and mitochondria-mediated apoptosis - Rentsendorj, Altan; Raedschelders, Koen; Fuchs, Dieu-Trang; Sheyn, Julia; Vaibhav, Vineet; Porritt, Rebecca A.; Shi, Haoshen; Dagvadorj, Jargalsaikhan; de Freitas Germano, Juliana; Koronyo, Yosef; Arditi, Moshe; Black, Keith L.; et al. (Frontiers in Immunology, 2023)
Introduction Osteopontin (OPN; also known as SPP1), an immunomodulatory cytokine highly expressed in bone marrow-derived macrophages (BMMΦ), is known to regulate diverse cellular and molecular immune responses. We previously revealed that glatiramer acetate (GA) stimulation of BMMΦ upregulates OPN expression, promoting an anti-inflammatory, pro-healing phenotype, whereas OPN inhibition triggers a pro-inflammatory phenotype. However, the precise role of OPN in macrophage activation state is unknown. Methods Here, we applied global proteome profiling via mass spectrometry (MS) analysis to gain a mechanistic understanding of OPN suppression versus induction in primary macrophage cultures. We analyzed protein networks and immune-related functional pathways in BMMΦ either with OPN knockout (OPNKO) or GA-mediated OPN induction compared with wild type (WT) macrophages. The most significant differentially expressed proteins (DEPs) were validated using immunocytochemistry, western blot, and immunoprecipitation assays. Results and discussion We identified 631 DEPs in OPNKO or GA-stimulated macrophages as compared to WT macrophages. The two topmost downregulated DEPs in OPNKO macrophages were ubiquitin C-terminal hydrolase L1 (UCHL1), a crucial component of the ubiquitin-proteasome system (UPS), and the anti-inflammatory Heme oxygenase 1 (HMOX-1), whereas GA stimulation upregulated their expression. We found that UCHL1, previously described as a neuron-specific protein, is expressed by BMMΦ and its regulation in macrophages was OPN-dependent. Moreover, UCHL1 interacted with OPN in a protein complex. The effects of GA activation on inducing UCHL1 and anti-inflammatory macrophage profiles were mediated by OPN. Functional pathway analyses revealed two inversely regulated pathways in OPN-deficient macrophages: activated oxidative stress and lysosome-mitochondria-mediated apoptosis (e.g., ROS, Lamp1-2, ATP-synthase subunits, cathepsins, and cytochrome C and B subunits) and inhibited translation and proteolytic pathways (e.g., 60S and 40S ribosomal subunits and UPS proteins). In agreement with the proteome-bioinformatics data, western blot and immunocytochemical analyses revealed that OPN deficiency perturbs protein homeostasis in macrophages—inhibiting translation and protein turnover and inducing apoptosis—whereas OPN induction by GA restores cellular proteostasis. Taken together, OPN is essential for macrophage homeostatic balance via the regulation of protein synthesis, UCHL1-UPS axis, and mitochondria-mediated apoptotic processes, indicating its potential application in immune-based therapies.